PWE-019 Day of admission results predict outcome in acute ulcerative colitis. (8th June 2018) - Arnott, Ian; Lynch, Ruairi; Manship, Thomas; Jagger, Fiona; Satsangi, Jack; Ho, Gwo-Tzer; Lees, Charlie; Grant, MissRebecca
Abstract : Introduction: Intravenous steroids remain the standard first line treatment for patients with acute ulcerative colitis (UC). However, 30% of patients fail to respond and require second line therapies and/or surgery. The purpose of this study was to determine if day 1 parameters could identify a group at high risk of failing first line therapies. Methods: All admissions for acute UC (ICD-10 K51) to hospitals within NHS Lothian (4 sites) from 1 st November 2015 to 31 st October 2016 were obtained from the regional coding department. Inclusion was limited to patients with UC as the primary reason for admission. Case record review confirmed diagnosis and clinical data were collected. Response to steroids was defined as discharge from hospital with no further acute medical or surgical treatment. The following parameters were recorded up to the first 10 days post admission: haemoglobin, platelet count, CRP, albumin, stool frequency, faecal calprotectin and abdominal x-ray results. Each patient was later attributed a score based on CRP (<50 mg/dL=0;>50 mg/dL=1), albumin (>30 g/L=0;<30 g/L=1) and platelets (<450×10 9 /L=0;>450×10 9 /L=1). Results: From 1 st November 2015 to 31 st October 2016 61 admissions with acute UC were identified; 37 (60%) of which responded to steroids, 24 (40%) patients were non-responders. 3 (12.5%) non-responders received infliximab as second line therapy, 1 (4.2%) adalimumab and 20 (83.3%) ciclosporin; 11 (45.8%) of the non-responders required surgery, 100% of whom had been previously treated with ciclosporin. On univariate analysis, the albumin, platelet count and CRP differed significantly between responders and non-responders (p≤0.05), whereas on multivariate analysis only CRP and albumin were significant. No difference was seen for haemoglobin and stool frequency. 88.9% of patients with concurrent hypoalbuminaemia, high CRP and high platelets (score=3) were non-responders. Conclusions: 82.4% of patients with a score of 2 or more will fail first line medical therapy. The combination of these readily available parameters identifies a high-risk population who may benefit from earlier second line medical or surgical intervention.